Development of a Holistic Learning Model Application (A Study on the Integration of Taḥsīn, Taḥfīẓ, and the Nahāwand Melody at Pondok Pesantren Taḥfīẓ Banten) - Nadra Ulfah; Utang Ranuwijaya; Deni Iriyadi; Fitri Hilmiyati; Wasehudin (Yayasan Darusssalam Bengkulu, 2026)
The application of a holistic learning model constitutes an effort to realize the comprehensive development of learners’ potential. Al-Qur’an teachers require a learning model that can develop the full potential of Qur’an memorizers. Qualified Qur’an memorizers are produced through a challenging and rigorous process. Various taḥsīn and taḥfīẓ methods have emerged to address the difficulties experienced by Qur’an memorizers. This study developed a holistic learning model application that integrates taḥsīn, taḥfīẓ, and the Nahāwand melody. The integration of taḥsīn, taḥfīẓ, and the Nahāwand melody resulted in a form of holistic learning that seeks to develop the potential of Qur’an memorizers comprehensively and in a balanced manner, encompassing intellectual, emotional, social, and spiritual aspects. The research methodology employed a systematic development approach by adopting the Borg and Gall model. The development process produced a learning model application packaged as a website-based application named husnunadzor.com. The implementation of the holistic learning model application, integrating taḥsīn, taḥfīẓ, and the Nahāwand melody, was conducted in three of the most prominent taḥfīẓ pesantren in Banten: Pondok Pesantren Taḥfīẓ Al-Afifah Rangkasbitung, Pondok Pesantren Taḥfīẓ Darul Huffaẓ Cikulur, and Pondok Pesantren Turus Pandeglang. The effectiveness of the holistic learning model application for students was examined through the results of a trial implementation of the learning model. The trial results were measured based on the students’ pre-test and post-test scores at Pondok Pesantren Taḥfīẓ Al-Afifah Rangkasbitung, Pondok Pesantren Taḥfīẓ Darul Huffaẓ Cikulur, and Pondok Pesantren Turus Pandeglang. The results showed that all students in the three pesantren experienced a significant increase in scores. Based on the data reduction results from questionnaires on implementation, practicality, and product effectiveness, the developed product indicated that the husnunadzor.com learning application has implications for students, Al-Qur’an teachers, and pesantren.